POLITIK KEMATIAN DALAM TAFSIR PRAKSIS STUDI KONSTALASI POLITIK FAKEM PALEMBANG DARUSSALAM DI ERA PILKADA KOTA PALEMBANG - Raden Ayu Erika Septiana (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2018)
As a majority religion, Islam has a special attraction for political actors. Because of the general behavior of Indonesian society based on the teachings contained in the Koran and al-Hadith. In the Indonesian political constellation, attracting public sympathy cannot be obtained easily and cheaply. Voice acquisition is sometimes not worth the effort that has been made. FAKEM Palembang Darussalam, is a phenomenon that teaches social power and its interaction with politics has provided valuable teaching that Islam with the teachings of help helps it can provide a way of establishing a political force that cannot be ignored